MEDIATION AS AN ALTERNATIVE METHOD OF DISPUTE RESOLUTION - Ibratova Feruza (Galaxy International Interdisciplinary Research Journal, 2023)
The article discusses issues of mediation, the principles of mediation, and analyzes legal acts on mediation issues. It is concluded that in the Republic of Uzbekistan, by legal nature, the legislator does not define this agreement as a civil transaction, in case of non-fulfillment or improper fulfillment of obligations under which the parties have the right to resort to the same methods of protection.